In the Upper Room: Metaphysics and Theology in Berkeley's Ethics - Airaksinen, Timo (Philosophy & theology, 2015)
This paper describes Berkeley’s ethics and analyses its metaphysical presuppositions. His ethical though is based on the theological idea of virtue that means obedience to God’s will and, hence, all ethically relevant concepts contain a reference to God. Berkeley also says that happiness in this vale of tears is God’s gift to us and a reward of virtue in heaven. Happiness is a sign and criterion of virtuous conduct. Obviously this kind of supernatural ethics can work only if its metaphysical foundation is so obvious that all decent people can figure it out. This is to say that revealed religion must be replaced by natural religion. According to Berkeley, the existence of God, his goodness, the reality of heaven, and its supreme happiness can be proved philosophically and in terms of natural religion. The main part of the paper describes and evaluates Berkeley’s logic, especially analogical reasoning and his inferences from conclusions to premises, or effects to causes. Another major theme is the mutual independence of revealed and natural theology. Berkeley’s minor writings are in a major role here. Due to the unsystematic nature of its sources the conclusions of this paper are open-ended and speculative.